Prognostic predictive value of preoperative intratumoral 2-deoxy-2-(18F)fluoro-D-glucose uptake heterogeneity in patients with high-grade serous ovarian cancer. Issue 10 (October 2018) - Liu, Shuai; Feng, Zheng; Jiang, Zhaoxia; Wen, Hao; Xu, Junyan; Pan, Herong; Deng, Yu; Zhang, Lei; Ju, Xingzhu; Chen, Xiaojun; Wu, Xiaohua
Abstract : Objective: This study aimed to explore the clinical and prognostic significance of pretreatment positron-emission tomography/computed tomography (PET/CT) parameters, especially 2-deoxy-2-( 18 F)fluoro-D-glucose-based heterogeneity, in high-grade serous ovarian cancer (HGSC). Materials and methods: We retrospectively investigated 56 patients with HGSC who underwent PET/CT before primary surgery at our hospital between January 2010 and June 2015. None of these patients received neoadjuvant chemotherapy. PET/CT parameters, including maximum and mean standardized uptake value (SUVmax and SUVmean ), metabolic tumor volume (MTV), total lesion glycolysis (TLG), and intratumoral heterogeneity index (HI), were measured for all patients. Differences of each PET/CT parameter between primary tumors (-P) and omental metastatic lesions (-M) were compared by paired t tests. Progression-free survival (PFS) and overall survival were analyzed by the Kaplan–Meier method and log-rank tests in univariate analyses. Cox regression analyses were used for multivariate analysis. Results: SUVmean -P was higher than SUVmean -M ( P =0.001). However, there were no statistical differences of SUVmax, MTV, TLG, or HI between primary and omental lesions. Chemosensitive patients tended to have higher levels of SUVmax -P ( P =0.011), MTV-P ( P =0.014), TLG-P ( P =0.035), and HI-P ( P =0.002), respectively. In univariate analyses, higher HI-P was associated with better PFS ( P =0.007). However, in multivariate analysis, HI-P was not an independent predictor of PFS ( P =0.581). Neither HI-P nor HI-M was the prognostic predictor for overall survival ( P =0.078 and 0.063, respectively). Conclusion: 2-Deoxy-2-( 18 F)fluoro-D-glucose-based heterogeneity appears to be a predictive and prognostic factor for patients with HGSC. Parameters of primary tumors have predominant value compared with omental metastatic lesions.